Comparative analysis of elastocaloric and barocaloric effects in single-crystal and ceramic ferroelectric (NH4)2SO4. (15th January 2021) - Mikhaleva, Ekaterina; Gorev, Mikhail; Bondarev, Vitaly; Bogdanov, Evgeny; Flerov, Igor
Abstract: We report the influence of anisotropy and texture on elasto(ElCE)- and baro(BCE)-caloric effects in single-crystal and ceramic (NH4 )2 SO4 . Inverse extensive and intensive ElCE in ceramics, (ΔSElCE )cer = 87 J/kg·K; ΔTAD = - 11.6 K), as well as in a single crystal along the ferroelectric axis a, (ΔSElCE )a = 115 J/kg·K; (ΔTAD )a = - 16 K, significantly exceed BCE, ΔSBCE = 75 J/kg·K; ΔTAD = - 9.8 K, even at low pressure 0.3 GPa. Caloric parameters of ammonium sulphate are comparable with those for promising solid-state refrigerants. Graphical abstract: Image, graphical abstract